Pengaruh GDP (Gross Domestic Product) dan Angka Harapan Hidup (AHH) terhadap IPM (Indeks Pembangunan Manusia) di Indonesia dan Brunei Darussalam - Widianningrum, Wahyu; Harahap, Raja Alamsyah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The Human Development Index (IPM) is a measure that measures a country's level of development based on three main dimensions: economic progress, social welfare, and health levels. GDP (Growth Domestic Product) and Life Expectancy (AHH) have a considerable influence on HDI. The purpose of this study is to compare the HDI between Indonesia and Brunei Darussalam and to find out factors such as AHH and GDP how much influence they have on HDI. The method used in this study is a quantitative method. The data collection method used was a literature review method based on secondary data obtained from the World Bank with a multivariable regression analysis model. The HDI of Indonesia and Brunei Darussalam is known to increase relatively every year, only in a few years it has decreased or has the same value. Factors such as AHH and GDP or GDP as a whole have influence and are related to HDI values. This can be seen in the test results obtained as in the normality test obtained by the two countries, which is proven to have normally distributed data, which illustrates that overall, for 30 years the HDI of the two countries has grown, although not significantly.